Mineralization of Carbon Dioxide: A Literature Review. Issue 4 (11th May 2015) - Romanov, Vyacheslav; Soong, Yee; Carney, Casey; Rush, Gilbert E.; Nielsen, Benjamin; O'Connor, William
Abstract Research on carbon capture and storage has been focused on CO2 storage in geologic formations, with many potential risks. An alternative to conventional geologic storage is carbon mineralization, where CO2 is reacted with metal cations to form carbonate minerals. Mineralization methods can be broadly divided into two categories: in situ and ex situ. In situ mineralization, or mineral trapping, is a component of underground geologic sequestration, in which a portion of the injected CO2 reacts with alkaline rock present in the target formation to form solid carbonate species. In ex situ mineralization, the carbonation reaction occurs above ground, within a separate reactor or industrial process. This literature review is meant to provide an update on the current status of research on CO2 mineralization.